Factors Associated with the Independence of Postpartum Mothers in Meeting Self-Care Needs - Puji Astutik (Indonesian Journal of Global Health Research, 2026)
Postpartum mothers’ independence in meeting self-care needs is an important indicator of maternal recovery and well-being. This study aimed to analyze the factors related to the level of independence among postpartum mothers in fulfilling self-care needs. A cross-sectional design was conducted in the Delima Ward of RSD Kertosono from January to May 2023, involving 91 postpartum mothers selected through purposive sampling. Data were collected using a structured questionnaire adapted from Nursalam (2020), which covered aspects of nutrition, activity, personal hygiene, perineal care, breast care, and elimination. Bivariate analysis was performed using the Chi-Square test to examine the relationship between independent variables (age, birth order, type of delivery, education, and information sources) and independence. The results showed that the majority of respondents were aged 25-35 years (42.9%) and primiparous (47.3%). Nearly half were categorized as dependent (47.3%), 34.1% needed assistance, and only 18.7% were independent. Type of delivery demonstrated the strongest association with independence (p=0.000; r=0.549), followed by education level (r=0.499) and information sources (r=0.449). Mothers who had spontaneous deliveries and higher education levels exhibited greater independence. In conclusion, type of delivery, education level, and information sources were identified as the dominant factors influencing postpartum mothers’ independence.